Factor Influencing Blood Pressure : A Study on Paluh Sibaji Fisherman in 2023 - Umi Salmah; Arfah Mardiana Lubis; Sri Malem Indirawati; Rusmalawaty Rusmalawaty; Halinda Sari Lubis; Najwa Nandita Dwinda; Dinda Fachrani Akri; Nisa Fadilla (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Non-communicable diseases (NCDs) are one of the main priorities in the world of health. As the world population soars, deaths from NCDs will increase every year. Globally, there are 41 million cases or the equivalent of 74% of deaths caused by NCDs every year. This research is a type of quantitative research with a cross-sectional type of research conducted on a group of fisherman in Paluh Sibaji Village. This research was carried out on September 21 2023. The population in this research was all fisherman in Paluh Sibaji Village, totaling 200 hundred fisherman. The sampling method used in this research was convenience sampling with a total of 60 fisherman respondents. This study aims to analyze the factors that influence fisherman's blood pressure on the incidence of hypertension (HTN). This research uses multiple linear regression analysis and application analysis using the Statistical Program for Social Sciences tools. The significance value of the consumption pattern, knowledge and attitude variables is below p<0.05, so it can be concluded that consumption pattern, knowledge and attitude influence the incidence of HTN among fisherman in Paluh Sibaji village. This study revealed that the majority of respondents, especially those belonging to the risk group, had experienced HTN. Age at risk was found to have a 2.26% higher likelihood of developing HTN. A large number of respondents showed poor consumption patterns, good knowledge, negative attitudes, and poor behavior regarding HTN prevention. These findings underscore the importance of targeted interventions and awareness campaigns to address these factors and reduce the risk of HTN in the studied population. It is recommended that further research discuss more broadly the factors that can influence the increase in blood pressure in fisherman and conduct a detailed food recall to assess the impact of consumption on HTN. Keywords: Attitude, Consumption pattern , Fisherman, HTN, Knowledge